Perceptions of Smallholder Farmers towards Organic Farming in South Africa - Solomon Eghosa Uhunamure (MDPI AG, 2021)
In South Africa, smallholder farming is an important aspect of livelihood. More so, organic farming is increasingly becoming popular among farmers. However, many studies undertaken focused on the trade possibilities of the industry leaving the farmers’ perceptions underrepresented. This study, therefore, aims to capture the farmers’ opinions by evaluating the critical factors and policy implications of organic farming in the Limpopo Province of South Africa. A total of 220 semi-structured questionnaires were administered to smallholder farmers in the province. The results revealed that organic farming is gaining recognition according to 82.8% of the participants, and 86.6% believed that organic farming has high-profit returns. However, 88.4% of the respondents agreed that the required standards for organic farming are too restrictive while a further 74.6% indicated that organic farming certification is difficult to obtain. The results also indicated a statistically significant difference in the perceived benefits of organic farming (p ≤ 0.001) and access to markets (p = 0.042). Based on the results, the study suggests more awareness, training and ease of certification as a way forward in changing the perceptions of the farmers in the province.